The relationship between ventilatory threshold and repeated-sprint ability in competitive male ice hockey players - Lowery, M. R.; Tomkinson, G. R.; Peterson, B. J.; Fitzgerald, J. S. (Journal of Exercise Science & Fitness, 2019)
The relationship between ventilatory threshold (VT1, VT2) and repeated-sprint ability (RSA) in competitive male ice hockey players was investigated. Methods: Forty-three male ice hockey players aged 18-23 years competing in NCAA Division I, NCAA Division III, and Junior A level participated. Participants performed an incremental graded exercise test on a skate treadmill to determine O2peak, VT1, and VT2 using MedGraphics Breezesuit™ software (v-slope). Participants performed an on-ice repeated shift (RSA) test consisting of 8-maximal skating bouts, lasting approximately 25 s and interspersed with 90 s of passive recovery, to determine first gate, second gate, and total sprint decrement (%dec). Pearson product-moment correlations and multiple regressions were used to assess relationships between ventilatory threshold variables (VT1, VT2, Stage at VT1, and Stage at VT2) and RSA (first gate, second gate, and total course decrement). Results: Stage at VT2 was the only variable substantially correlated with first gate (r = -0.35; P < 0.05), second gate (r = -0.58; P < 0.001) and total course decrement (r = -0.42; P < 0.05). Conclusion: The results of this study demonstrated that VT is substantially associated with RSA, and VT2 is more strongly correlated with RSA than O2peak. This study suggests that longer duration high-intensity interval training at intensities that increase workrate at VT2 may lead to possible improvements in RSA.